El edificio moderno en Medellín, el confort y el cambio climático. - Murillo López , Gustavo (2024)
Climate change is the problem that affects man's natural environment, his health and his existence worldwide. The increase in temperature, energy demands and pollution have led to concern about the human practices causing this environmental crisis, but they have especially promoted the development of sustainable practices in various fields of knowledge, including architecture. Since the end of the 19th century, but especially at the beginning of the 20th century with the modern movement, methods and strategies were already being developed by architects that allowed buildings to be adapted to the climate, using strategies to illuminate and ventilate naturally, establishing Thus, an adequate relationship between architecture and its natural environment, therefore, the aim is to evaluate the response to thermal and visual comfort of a modern building in the city of Medellin by analyzing its formal strategies for adaptation to the climate from its initial conditions to the current ones. environmental conditions. To carry out this, a mixed methodology was established, that is, one qualitative and one quantitative. The first allowed an approach to the case study building from the approaches of modernity and thus understand the formal strategies of the shadow devices. The second allowed computer simulations to be carried out to analyze thermal and visual comfort in the current environmental conditions of the building. It was concluded that the design of shading devices for adaptation to the climate of the chosen building provides adequate conditions of thermal and visual comfort in the current environmental conditions as a result of the conscious exercise of the local architects of the time in which the building was designed.